Indoor air quality and thermal comfort-results of a pilot study in elderly care centers in Portugal - Mendes, A. (2014)
The age of the European population is rising and percentage of adults aged 65 years and older is projected to increase from 16% in 2000 to 20% in 2020. It has been estimated that older subjects spend approximately 19 to 20 h/d indoors. Older individuals may be particularly at risk for detrimental effects from pollutants, even at low concentrations, due to reduced immunological defenses and multiple underlying chronic diseases. Six Porto, Portugal, urban area elderly care centers (ECC), housing a total of 425 older persons, were studied to assess indoor air quality (IAQ) and thermal comfort (TC) in two seasons. This study presents the IAQ and TC results in 36 rooms and constitutes part of a wider and ongoing study. The study areas were all naturally ventilated, and indoor concentrations in winter were within Portuguese reference values. However, 42% of the participants were dissatisfied with indoor thermal conditions, rating it "slightly cool." In summer, the index rate of dissatisfied individuals was lower (8%). Significant differences were found between seasons in predicted percent of dissatisfied people (PPD) and predicted mean vote (PMV) indices. Fungal concentrations frequently exceeded reference levels (>500 colony-forming units [CFU]/m(3)). In addition, other pollutants occasionally exceeded reference levels. To our knowledge, this is the first study in Portugal to assess effects of indoor air contaminants on the health status and quality of life in older subjects living in ECC. Although IAQ and TC parameters were mostly within reference values, the results suggest a need to improve the balance between IAQ and TC in ECC, a critical environment housing a susceptible population.